Goal matching in couple therapy: individual and couple level trajectories - Smith, Amy D., author; Quirk, Kelley, advisor; Haddock, Shelley, committee member; Steger, Michael, committee member (Colorado State University. Libraries, 2018)
In couple therapy, the degree to which partners are aligned in their therapy goals is important and is understudied in the psychotherapy literature. Individual and couple level factors likely influence whether a couple has matched or mismatched goals at the first session. These factors include open expression and flexibility of each individual partner, as well as the relational factors of commitment and sexual satisfaction. The therapeutic alliance was also examined to investigate the association with belonging to a relationship with matched versus mismatch goals. Data were gathered from couples who were in naturalistic couple therapy, from sessions one through ten. Growth models were performed to examine base line differences and trajectory differences between goal matched versus goal mismatched groups. Results revealed that couples reported significantly lower commitment and sexual satisfaction in the goal mismatched group, as compared to the goal matched group, at the initial therapy session, and no significant trajectory differences were found between these two groups for these variables across sessions. In addition, those in the goal matching group reported higher ratings of the individual alliance and between partners alliance (within-alliance) at the initial session. As sessions progressed, couples in the goal mismatch group displayed significantly higher within-alliance ratings, as compared to those couples in the matched group. These data suggest that couples with matched versus mismatched therapy goals start therapy in different places in regard to commitment and sexual satisfaction, and therapist may play an important role in helping couples become more aligned as therapy progresses. Implications for therapists who are working with couples that present with goal match or mismatch are offered.